Common Errors in Digital Panoramic Radiographs of Patients with Mixed Dentition and Patients with Permanent Dentition - Benjamin Peretz; Maya Gotler; Israel Kaffe (International Journal of Dentistry)
Purpose. To compare errors in digital panoramic radiographs of permanent and mixed dentitions. Methods. 143 and 146 digital radiographs of mixed and permanent dentitions were examined. Results. Significantly fewer errors presented in the mixed dentition. Positioning too forward significantly prevalent in the mixed dentition; slumped position and nonpositioning of chin properly were significantly prevailed in the permanent dentition. Blurred or shortened upper incisors were significantly more prevalent in the mixed dentition. Diagnostic ability could be improved by manipulating the brightness or contrast in nearly 45% of all radiographs. In the mixed dentition, tilting the chin down and a slumped position made the lower incisors significantly nondiagnostic. In the permanent dentition, tilting the chin down made the lower incisors to be significantly nondiagnostic. Conclusions. More errors were prevalent in panoramic radiographs of permanent dentitions. Properly positioning the patient is the most important factor in preventing a cascade of errors.